Foliar water-uptake strategies are related to leaf water status and gas exchange in plants from a ferruginous rupestrian field - Boanares, Daniela; Kozovits, Alessandra R.; Lemos-Filho, José P.; Isaias, Rosy M. S.; Solar, Ricardo R. R.; Duarte, Alexandre A.; Vilas-Boas, Tiago; França, Marcel G. C. (American journal of botany, 2019)
Premise Fog is a frequent event in Brazilian rupestrian field and plays an important role in the physiology of several plant species. Foliar water uptake (FWU) of fog may be fast or slow depending on the species. However, fog water may negatively affect CO2 assimilation. Thus, the interference in the water and carbon balance as a result of different strategies of FWU was evaluated to verify whether fog may mitigate possible water deficit in leaves. Methods Four plant species with different FWU strategies were studied in a ferruginous rupestrian field with frequent fog. Gas exchange and water potential were measured before dawn and at midday during the dry and rainy seasons, separating foggy from non‐foggy days during the dry season. Results The FWU speed negatively influences CO2 assimilation in the dry season, possibly because of its negative relationship with stomatal conductance, since reduced stomatal aperture impairs carbon entrance. Fog presence increased leaf water potential both in early morning and midday during the dry season. However, during the rainy season, the values of leaf water potential were lower at midday, than during the dry season with fog at midday, which favors leaf gas exchanges. Conclusions FWU interferes negatively, but briefly with CO2 assimilation. Nevertheless, FWU prevents water loss through transpiration and increases the water status of plants in the dry season. That is, FWU results in a compensation between CO2 assimilation and foliar hydration, which, in fact, is beneficial to the plants of this ecosystem.